2008
DOI: 10.1542/peds.2007-2553
|View full text |Cite
|
Sign up to set email alerts
|

Frenulotomy for Breastfeeding Infants With Ankyloglossia: Effect on Milk Removal and Sucking Mechanism as Imaged by Ultrasound

Abstract: Infants with ankyloglossia experiencing persistent breastfeeding difficulties showed less compression of the nipple by the tongue postfrenulotomy, which was associated with improved breastfeeding defined as better attachment, increased milk transfer, and less maternal pain. In the assessment of breastfeeding difficulties, ankyloglossia should be considered as a potential cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
170
0
23

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(196 citation statements)
references
References 27 publications
3
170
0
23
Order By: Relevance
“…Ultrasound and vacuum measurement confirmed that the infant-sucking dynamic may be affecting milk transfer and supported previous findings by Geddes et al 21 in which maternal nipple distortion and limited tongue movement in infants with ankyloglossia resulted in feeding problems, which resolved postfrenotomy along with an increase in infant milk transfer. The intraoral vacuums were within the normal range 23 prefrenotomy, suggesting that compression of the base of the nipple may have contributed to lower milk transfer.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Ultrasound and vacuum measurement confirmed that the infant-sucking dynamic may be affecting milk transfer and supported previous findings by Geddes et al 21 in which maternal nipple distortion and limited tongue movement in infants with ankyloglossia resulted in feeding problems, which resolved postfrenotomy along with an increase in infant milk transfer. The intraoral vacuums were within the normal range 23 prefrenotomy, suggesting that compression of the base of the nipple may have contributed to lower milk transfer.…”
Section: Discussionsupporting
confidence: 87%
“…Postfrenotomy pinching of the base of the nipple was not observed. 21 The infant applied stronger baseline and peak pressures during nutritive and nonnutritive sucking prefrenotomy during breastfeeding, compared with both feeding with the Calma teat (prefrenotomy) and breastfeeding postfrenotomy, where pressures were reduced by approximately half (Table 2). Suck-burst duration was much shorter during breastfeeding prefrenotomy.…”
Section: Patient Presentationmentioning
confidence: 99%
“…This maternal perception is based in fact: collection does take energy from both the baby and the mother. Under normal nutritional situations, such loss is relatively minor and likely compensated by the mammary gland that day or at a minimum over the next several days (Geddes et al, 2008;Kent et al, 2006). However, in limited nutritional contexts, the resulting deficit may be more severe, especially if repeated measures or a full mammary expression are used.…”
Section: Ethical and Practical Issuesmentioning
confidence: 99%
“…Ambos são procedimentos simples com baixa possibilidade de complicações pós-operatórias. A técnica empregada na frenotomia consiste de anestesia tópica da mucosa do freio lingual, seguida de incisão de 3 a 4 milímetros de profundidade na região mais delgada do mesmo, por ser pouco vascularizada 5 . Os benefícios do procedimento para o bebê são melhora na postura e mobilidade da língua, e na postura do lábio o que contribui para garantir os benefícios da amamentação, como o ganho de peso, através do correto vedamento do lábio no mamilo 23 .…”
Section: Tratamento Cirúrgico Da Anquiloglossiaunclassified
“…Em lactentes, a anquiloglossia pode gerar dificuldades na amamentação, uma vez que a deglutição e sucção estão relacionadas a este processo. Essa situação pode chegar a causar dificuldade de ganho de peso da criança e dor no mamilo da mãe durante o ato de amamentar, e assim, levar a um desmame precoce e prejuízo do desenvolvimento normal da criança 2,4,5 . Além disso, podem também ocorrer limitações do movimento da língua durante o choro e a lalação e posteriormente, dificuldades de dicção 3 .…”
Section: Introductionunclassified